Comparative study of minutiae selection methods for digital fingerprints - Vibert, Benoit; Le Bars, Jean-Marie; Charrier, Christophe; Rosenberger, Christophe (Frontiers in Big Data, 2023)
Biometric systems are more and more used for many applications (physical access control, e-payment...). Digital fingerprint is an interesting biometric modality as it can easily be used for embedded systems (smartcard, smartphone, smartwatch). A fingerprint template is composed by a set of minutiae used for their comparison. In embedded systems, a secure element is in general used to store and compare fingerprint templates to meet security and privacy requirements. Nevertheless, it is necessary to select a subset of minutiae from a template due to storage and computation constraints. We present in this paper, a comparative study of the main minutiae selection methods from the literature. The considered methods require no further information like the raw image. Experimental results show their relative performance when using different matching algorithms and datasets. We identified that some methods can be used within different contexts (enrollment or verification) with a minimal degradation of performance.